plan de mercadeo para incrementar la cartera de clientes de la empresa calzado sin fin, en el cantón santo domingo, año 2015 - Zambrano Alcívar, Jessenia Fabiola (2015)
The development of a country depends on the companies and these in turn on the company, for such a motive it is necessary that the organizations introduce his procedures for the manufacture or commercialization of products, performing great importance the creation of plans that help to the transformation of the same ones and for increasing the clients' portfolio allowing them to approach day after day the attainment of his aims. The conditions of the market make indispensable the production of plans of marketing, not being the exception the company worn WITHOUT END since across the same one it will be announced and will be able to increase the quantity of current clients that it possesses. The detection of the problems that they afflict to the company worn WITHOUT END as the lack of campaigns of advertising, scanty promotion, few sellers and not to take part in fairs of exhibition they decided by means of the utilization of Ishikawa's technology. The reasons that generate the problem in the company object of study were sustained in the development of the methodology using types, methods, technologies and instruments that determined the feasibility of the development of the offer. They propose the strategies that compose the Plan of Marketing for the company worn WITHOUT END by means of the analysis of the environment that allows to detect the reasons of the problem, there being designed this way the actions to be still related to the cost-benefit and being applied in the short term. In the analysis of results there was demonstrated that the market considers to be like positive that the company should realize the sale of footwear door to door across sellers, the participation in fairs decided as feasibly exhibitions, finally the advertising and promotion are important factors that affect for the purchase of footwear. Key words: Investigation of markets, situational Analysis, Strategies of market, Action plans and clients' Portfolio.